The Effect of Mixing Parameters on The Stability of Carbopol-Based Emulsions to Maintain Product Quality in a Cosmetic Company - Israyandi Israyandi; Devina Aulia Putri; Setyanisha Supadi (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Emulsion stability is one of the key parameters in cosmetic formulation because it is directly related to product quality and consistency during storage. In Carbopol-based emulsion systems, the mixing process plays a major role in forming the gel structure and in the rheological properties of the final product. This study aims to examine the effect of mixing-speed variation on the viscosity and stability of a Carbopol system neutralized using NaOH. The mixing process was carried out at speeds of 1000, 1100, and 1200 rpm for 10 minutes, with a relatively constant Carbopol concentration. The observed parameters included changes in pH and emulsion viscosity, measured using a viscometer. The results show that all samples met the company’s pH and viscosity standards, with a mixing speed of 1100 rpm producing the highest viscosity value. These findings indicate that setting the appropriate mixing speed is essential for obtaining optimal emulsion stability in Carbopol-based cosmetic formulations.